2008
DOI: 10.1016/j.cemconcomp.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shrinkage of cement pastes and mortars at very early age: Effect of limestone filler and granular inclusions

Abstract: This article presents a study on the influence of limestone filler and granular inclusions on the chemical shrinkage of cementitious matrices at very early age (624 h). Measurements of chemical shrinkage and hydration degree are carried out on cement pastes and mortars. During this study, two cement types (CEM 1 and CEM 2), two water-to-cement ratios (W/C = 0.30 and 0.40) and three substitution rates of cement by limestone filler (LF/C = 0; 0.25 and 0.67) are used. The effects of aggregate shape (glass beads a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(65 citation statements)
references
References 21 publications
(29 reference statements)
1
48
1
2
Order By: Relevance
“…The presence of limestone powder and natural pozzolan causes an acceleration of the autogenous shrinkage and the hydration process since the very early age. This effect is generally explained by supplementary surface activity provided by the mineral addition particles, creating nucleation sites for hydrates as reported by others researchers [18,19]. At this age, autogenous shrinkage for mortars with slag remains lower than that of ordinary cement for all replacement rates.…”
Section: Discussionmentioning
confidence: 65%
“…The presence of limestone powder and natural pozzolan causes an acceleration of the autogenous shrinkage and the hydration process since the very early age. This effect is generally explained by supplementary surface activity provided by the mineral addition particles, creating nucleation sites for hydrates as reported by others researchers [18,19]. At this age, autogenous shrinkage for mortars with slag remains lower than that of ordinary cement for all replacement rates.…”
Section: Discussionmentioning
confidence: 65%
“…The rheological parameters of hydrating suspensions were determined from the flow curves taken with a rotational viscometer. Some selected samples were subjected to the evaluation of the so-called chemical shrinkage, using basic laboratory equipment (glass vials and pipettes) and procedure similar to that given in the ASTM Standard C 1608-07 [12,13]. Some samples were observed under SEM with EDS microanalyzer, to characterize the microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of limestone have been observed to alter aspects of the cement performance through the proposed mechanisms of dilution, the filler effect (particle packing), and nucleation (4,6,(17)(18)(19)(20)(21)(22)(23). Many authors have observed that these mechanisms affect the hydration of the cement, subsequently modifying the performance of the overall system (4,6,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). It is important to note that these mechanisms are interrelated and act simultaneously, influencing many of the same parameters of the system.…”
Section: Mechanisms Associated With Limestone Replacements In Cementmentioning
confidence: 99%